Impacto da saúde bucal, variáveis socioeconômicas e demográficas, tratamentos oncológicos e seus efeitos deletérios sobre a qualidade de vida relacionada à saúde de portadores de câncer infantil - Carneiro, Tamires Vieira (2014)
INTRODUCTION: The treatment of childhood cancer shows up increasingly effective, but on the adverse effects of therapy, which also benefits the oral cavity, the quality of life related to health (HRQOL) of patients may suffer. OBJECTIVE: To evaluate the impact of oral health, socioeconomic and demographic, cancer treatments and its deleterious effects on HRQoL of patients with childhood cancer. METHODS: A cross-sectional study was conducted in a referral hospital in the state of Paraiba, using as instruments to collect the chips (clinical examination and interview) SB Brasil 2010 and the Oral Assessment Guide modified. Data on HRQoL were collected in interviews applying the instrument PedsQLTM versions 3.0 and 4.0. Sought out the medical records information related to neoplasia base and treatment. The survey was conducted in September/2013 to September/2014. Data were analyzed using descriptive and inferential statistics, through the binary logistic regression, which identified the significant variables to explain HRQOL of the study patients. RESULTS: The sample was selected by convenience, consisting of 100 patients aged 2 to 18 years and their caregivers. Behaved as protective factors for the impairment in HRQoL of patients in treatment, in view of the caregivers, have fewer difficulties in the areas pain and injuries (OR = 0.96), anxiety treatment (OR = 0.96) and nausea (OR = 0.94), and risk factors, the increase in the number of people in the household (OR = 1.76) and the feeling of a lot of dissatisfaction with the teeth (OR = 10.43). Also in view of the caregivers in patients with completed treatment, the perception of physical appearance (OR = 0.96) behaved as a protective factor, and the feeling of a lot of dissatisfaction with the teeth (OR = 12.8), as a factor risk. In the view of caregivers of patients being treated and completed treatment, there were as protective factors, have fewer cognitive difficulties (OR = 0.92), pain and injuries (OR = 0.94), anxiety procedures (OR = 0.93), and risk factors, being female (OR = 9.49), number of people in the household (OR = 1.94) and ashamed to smile (OR = 13.82). In the view of patients in treatment and completed treatment, behaved as protective factors, have fewer difficulties in the cognitive domain (OR = 0.94) and in the perception of physical appearance (OR=0.94), as risk factors, ashamed to smile (OR = 11.56) and toothache (OR = 7.37). CONCLUSION: In relation to oral health, behaved as risk factors for impaired HRQOL of study patients: the feeling of a lot of dissatisfaction with the teeth, ashamed to smile, and toothache. Among the other variables, such as protective factors, it was observed: minor difficulties in pain and bruised areas, anxiety treatment, anxiety procedures, nausea, cognitive, perception of appearance. You can even say that being female and increasing the number of people in the residence are risk factors for the same.